Evaluating gender-based mobile shopping application using eye-tracking technology - Aslina Baharum; Emelia Abdul Rahim; Rozita Hanapi; Noorsidi Aizuddin Mat Noor; Nurhafizah Moziyana Mohd Yusop (Institute of Advanced Engineering and Science, 2019)
The mobile applications (apps) development has been gaining popularity for the past few years. Some mobile apps have been failing in its popularity because of the unattractive user interface and bad interaction with the apps. This was proven by previous researchers who have stated that the interaction between a user of mobile application and a graphical user interface could lead to some misunderstandings, errors and frustration from an inability to achieve a goal and could lead to failure of the mobile application. Most of the mobile application developers have been facing proper graphical user interface design recently. There is a noticeable lack of studies and research in the area of mobile application design compared to web application user interface (UI) design. Therefore, this research was done to evaluate the different gender on the mobile shopping application using eye-tracking technology. This research had proposed guidelines based on gender for mobile shopping application. These proposed guidelines can be preferred in the designing process of a mobile shopping application as it could provide a better user interaction and would prevent failure in its popularity by providing fast and user friendly interface.